1993-1995 IRRI rice almanac (International rice research institute, 1995)
This book is a compendium on rice, bringing together information on its origin and diffusion, its growth and production, the ecosystems under which it is grown, and the opportunities for increased yield and production. Subjects discussed include: (1) the genetic diversity of rice; (2) rice-growing areas; (3) the importance of rice as human food; (4) speciality uses of rice; (5) the morphology and growth of the rice plant; (6) wetlands and rice soils; (7) the various rice production environments and agro-ecological zones; (8) the role of IRRI in rice research; and (9) some new research tools, such as biotechnology, crop modelling and geographic information systems. The main rice-producing countries are discussed separately, with information on the importance of rice in the country, the rice environment, production constraints, production opportunities, and production data. Tables are appended with data on the area and production of rice and other cereals by agro-ecological zones in Asia, and the distribution of rice area by ecosystem. Important conversion factors for data from various countries are provided